Computational STAT4 rSNP Analysis, Transcriptional Factor Binding Sites and Disease - Norman, E. Buroker (Journal of Bioinformatics And Diabetes, 2016)
Purpose Signal Transducer and Activator of Transcription 4 (STAT4) is important for signaling by interleukins (IL-12 and IL-23) and type 1 interferons and has been found to have several simple nucleotide polymorphisms (SNPs) associated with human disease. STAT4 SNPs were computationally examined with respect to changes in potential transcriptional factor binding sites (TFBS) and these changes were discussed in relation to human disease. Methods The JASPAR CORE and ConSite databases were instrumental in identifying the TFBS. The Vector NTI Advance 11.5 computer program was employed in locating all theTFBS in theSTAT4 gene from 4 kb upstream of the transcriptional start site to 8.3 kb past the 3’UTR. The JASPAR CORE database was also involved in computing each nucleotide occurrence (%) within the TFBS. Results The STAT4 SNPs in the 70 kb intron between exon 2 and 3 are in linkage disequilibrium and have previously been found to be significantly associated with several vasculitis diseases as well as diabetes. The SNP alleles were found to alter the DNA landscape for potential transcriptional factors (TFs) to attach resulting in changes in TFBS and thereby, alter which transcriptional factors potentially regulate the STAT4 gene. These STAT4 SNPs should be considered as regulatory (r) SNPs. Conclusion The alleles of each rSNP were found to generate unique TFBS resulting in potential changes in TF STAT4 regulation. These regulatory changes were discussed with respect to changes in human health that result in disease.
Keywords: STAT4; rSNPs; TFBS; disease